VOICE OF CUSTOMER TENTANG STUDENT CENTER UNIVERSITAS KRISTEN PETRA (Civil Engineering Dimension, 2004)
Petra Christian University plans to build a Student Center, which functions as a place for students togather in an informal meeting, a place for student activities, and a place with social and culturalfacilities for students, but still fit with the purpose of the university. To prepare a more suitable planfor the students as the main users, their voices should be considered. A survey to 1087 students hasbeen done to gather their voices.This study evaluates level of need and level of importance of the room that will be provided in theStudent Centre. The level of satisfaction of the existing facilities’ size has been evaluated to thestudent guild.This study has recommended rooms under seven categories which have to be provided, such as: roomsfor student union, academic support, administration, social, religious rooms, commercial room andsome complementary rooms Abstract in Bahasa Indonesia : Universitas Kristen Petra merencanakan untuk mendirikan Student Center yang merupakantempat berkumpulnya mahasiswa dan sivitas akademika dalam pertemuan informal, tempataktivitas mahasiswa dan tempat yang menyediakan fasilitas rekreasi, sosial, dan kultural sesuaidengan dasar dan tujuan universitas. Agar perencanaanya lebih sesuai dengan kebutuhanpengguna utamanya, yaitu mahasiswa, maka pendapat mereka perlu menjadi bahan pertimbangan.Untuk mengetahui pendapat mahasiswa telah dilakukan survey kepada 1087 responden mahasiswaaktifis dan non aktifis.Studi ini menilai tingkat kebutuhan dan tingkat kepentingan dari ruangan yang akan disediakan didalam Student Center tersebut. Mengingat sebagian ruangan-ruangan tersebut sudah ada, makadilakukan juga evaluasi kepuasan pengguna ruangan terhadap luas ruangan yang diwakili olehaktivis mahasiswa.Hasil akhir dari penelitian ini adalah rekomendasi ruangan yang perlu disediakan dapatdikategorikan sebagai ruangan untuk organisasi mahasiswa, ruang penunjang akademik, ruangspriritual, ruang administrasi, ruang sosial dan dilengkapi dengan beberapa ruang komersial sertaruang pelengkap.